2003
DOI: 10.1074/jbc.m303022200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Acid Sphingomyelinase through Modification or Deletion of C-terminal Cysteine

Abstract: One form of Niemann-Pick disease is caused by a deficiency in the enzymatic activity of acid sphingomyelinase. During efforts to develop an enzyme replacement therapy based on a recombinant form of human acid sphingomyelinase (rhASM), purified preparations of the recombinant enzyme were found to have substantially increased specific activity if cell harvest media were stored for several weeks at ؊20°C prior to purification. This increase in activity was found to correlate with the loss of the single free thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
122
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 38 publications
6
122
0
Order By: Relevance
“…This notion is consistent with a previous biochemical study (Qiu et al, 2003) indicating that oxidation of purified ASM at cysteine 629 results in stimulation and a disulfide bond-mediated dimerization A central role of ROS for the induction of apoptosis by CD95 has been previously reported (Gulbins et al, 1996;Um et al, 1996) and was recently confirmed by several studies (Reinehr et al, 2005;Yin, 2005). Experiments on hepatocytes demonstrated that an inhibitor of the ASM blocks the release of ROS suggesting that ROS functions downstream of the ASM (Reinehr et al, 2005;Yin, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…This notion is consistent with a previous biochemical study (Qiu et al, 2003) indicating that oxidation of purified ASM at cysteine 629 results in stimulation and a disulfide bond-mediated dimerization A central role of ROS for the induction of apoptosis by CD95 has been previously reported (Gulbins et al, 1996;Um et al, 1996) and was recently confirmed by several studies (Reinehr et al, 2005;Yin, 2005). Experiments on hepatocytes demonstrated that an inhibitor of the ASM blocks the release of ROS suggesting that ROS functions downstream of the ASM (Reinehr et al, 2005;Yin, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…However, further details of the stimulation of neutral sphingomyelinase are presently not known. The acid sphingomyelinase is activated by oxidation [43, 50, 72]. It is unknown whether the protein is directly oxidized in vivo or regulated via pathways that are redox-sensitive.…”
Section: Sphingomyelinasesmentioning
confidence: 99%
“…It is unknown whether the protein is directly oxidized in vivo or regulated via pathways that are redox-sensitive. Scavengers of reactive oxygen intermediates prevent activation of the acid sphingomyelinase by stimuli such as DR5 or Cu 2+ [43, 50, 72]. In vitro studies by Qui et al .…”
Section: Sphingomyelinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been suggested that carboxyl-terminal modification of aSMase might serve as a mechanism to regulate enzyme activity. Qiu et al (8) described a mechanism whereby oxidation, mutation, and/or deletion of the C-terminal Cys 629 resulted in activation of the enzyme. Based on these results the authors postulated that loss of the C-terminal Cys 629 might serve as a "cysteine switch," as has been described for matrix metalloproteinases (9), whereby loss of C-terminal Cys residues favors hydration of Zn 2ϩ thereby promoting enzyme activation (8).…”
mentioning
confidence: 99%